2021
DOI: 10.1139/bcb-2020-0641
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose lipopolysaccharide protects nerve cells against spinal cord injury via regulating the PI3K–AKT–Nrf2 signaling pathway

Abstract: This study explored the molecular mechanism behind the protective effects from low-dose lipopolysaccharide (LPS) on an in-vitro model of spinal cord injury (SCI). For this, PC12 cells were treated with different concentrations of LPS and the cell counting kit-8 assay was used to measure the toxicity of LPS to the cells. Next, we used immunofluorescence to measure nuclear translocation of Nrf2 in PC12 cells. PC12 cells were then treated with IGF-1 (PI3K agonist) and LY294002 (PI3K inhibitor). An in-vitro model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Li et al found that low-dose lipopolysaccharide protected nerve cells against SCI by regulating the PI3K-AKT-Nrf2 signaling pathway. [26] Studies have reported that curcumin can inhibit the TGFβ-SOX9 and Wnt/mTOR signaling pathways, promote motor function recovery after injury, reduce neuronal apoptosis, and play a neuroprotective role. [27,28] All these studies are consistent with our results, which verified the SCI repair function of PF-SA-GAD.…”
Section: Pf-sa-gad Alters the Expression Of Genes Related To Sci Repairmentioning
confidence: 99%
“…Li et al found that low-dose lipopolysaccharide protected nerve cells against SCI by regulating the PI3K-AKT-Nrf2 signaling pathway. [26] Studies have reported that curcumin can inhibit the TGFβ-SOX9 and Wnt/mTOR signaling pathways, promote motor function recovery after injury, reduce neuronal apoptosis, and play a neuroprotective role. [27,28] All these studies are consistent with our results, which verified the SCI repair function of PF-SA-GAD.…”
Section: Pf-sa-gad Alters the Expression Of Genes Related To Sci Repairmentioning
confidence: 99%
“…In PC12 cells, low-dose LPS has been shown to inhibit apoptosis, as evidenced by the downregulation of pro-apoptotic caspase 3 and caspase 9 and the upregulation of anti-apoptotic HO-1, NQO1, and γ-GCS proteins. Low-dose LPS treatment has also been shown to reduce the apoptotic rate and decrease oxidative stress levels by activating the PI3K-AKT-Nrf2 signaling pathway in an in vitro PC12 cell model of SCI [ 45 ]. These results highlight the therapeutic potential of low-dose LPS administration in SCI, although further studies are needed to elucidate the underlying mechanisms beyond beneficial effects.…”
Section: Beneficial Effects Of Low-dose Lps Treatment On Neurons Cell...mentioning
confidence: 99%
“…Interestingly, low-dose LPS can induce a protective cross-tolerance state, which has a protective effect on subsequent injury (Jacob et al, 2016). Studies have shown that low-dose LPS pretreatment has a neuroprotective effect (Longhi et al, 2011;Li et al, 2013), and its mechanism has been proven to be through activation of the PI3K-Akt-Nrf2 signaling pathway, thereby reducing the rate of apoptosis and inhibiting Oxidative stress (Li W. et al, 2021).…”
Section: Lipopolysaccharidementioning
confidence: 99%